Compound heterozygous variants of the FBXO7 gene resulting in infantile‐onset Parkinsonian‐pyramidal syndrome in siblings of a Chinese family. Issue 8 (10th April 2020) - Jin, Xiaohua; An, Lisha; Hao, Shengju; Liu, Qian; Zhang, Qinhua; Wang, Xing; Feng, Xuan; Zhang, Chuan; Cao, Xiaofang; Yan, Yousheng; Ma, Xu
Abstract: Background: Mutations in the FBXO7 gene can cause a rare chromosomal recessive neurodegenerative disease, Parkinsonian‐pyramidal syndrome (PPS). Patients with this syndrome mainly show early‐onset Parkinson's syndrome. Here, we present a Chinese family with infantile‐onset PPS caused by FBXO7 mutations. Methods: The clinical phenotypes and medical records of the proband and his family members were collected. The proband, his sibling, and his parents underwent whole‐exome sequencing (WES) by next‐generation sequencing. Results: The proband and his sibling had a typical PPS phenotype with onset during infancy. WES identified compound heterozygous variants in the FBXO7 gene, including a nonsense mutation, p. Trp134*, and a splicing mutation, IVS5‐1G > A, which were shared by both siblings and inherited from each of the parents. These variants have not been reported in literatures or databases. According to the American College of Medical Genetics and Genomics guidelines, the p. Trp134* and IVS5‐1G > A mutations were classified as pathogenic variants. Conclusions: We report a case of siblings in a Chinese family with infantile‐onset PPS caused by FBXO7 gene mutations determined by WES. These findings will contribute to the in‐depth study of the pathogenesis of PPS among patients with FBXO7 gene mutations.